Pseudarge taurica sp. n. from Crimea, and a new synonymy in Pseudarge Gussakovskij, 1935 (Hymenoptera: Argidae) - S.A. Basov (Кавказский энтомологический бюллетень)
Pseudarge taurica sp. n. is described from Crimea. Tis is the frst species of the genus Pseudarge Gussakovskij, 1935 known from the territory of Crimea and the second in the fauna of Russia. Te new species is distinguished from Pseudarge species found in Central Asia and Southern Europe by its completely black head and dark thorax with a blue metallic reflection. Te new synonymy is introduced: Pseudarge rubicunda Gussakovskij, 1935 = Arge tigrata Blank, Liston et Taeger in Blank et al., 2009, syn. n.